Direction of Trade Statistics Yearbook, 1975 Edition. (Direction of Trade Statistics; Direction of Trade Statistics, 1975)
This paper discusses the tenth Direction of Trade Annual (DOT), provides trade-by-country data for the years 1970 through 1974 for 167 countries, and summaries of the trade of these countries with the world and with 11 areas, firstly, as they can be made from the summation of the data on the country pages for the countries of a given area or of the world, and, secondly, as they can be made from the summation of the data on all country pages by taking from each page the data reporting trade with a given area or with the world. The data for the total exports and imports of each country and the area and world totals are conceptually equal to International Financial Statistics (IFS) trade data, which are also reported for comparison at the top of each area and country page in this volume.